Asymptotic equivalence and sufficiency for volatility estimation under microstructure noise - Markus Reiß (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The basic model for high-frequency data in finance is considered, where an efficient price process is observed under microstructure noise. It is shown that this nonparametric model is in Le Cam's sense asymptotically equivalent to a Gaussian shift experiment in terms of the square root of the volatility function .... As an application, simple rateoptimal estimators of the volatility and efficient estimators of the integrated volatility are constructed.
Keywords: C14; C58; 330; high-frequency data; integrated volatility; spot volatility estimation; Le Cam deficiency; equivalence of experiments; Gaussian shift; Finanzmarkt; Volatilität; Zeitreihenanalyse; Nichtparametrisches Verfahren; Schätztheorie; Mikrostrukturanalyse; Noise Trading; Theorie